Avaliação do perfil nutricional, metabólico e dos hábitos de sono de médicos em programa de residência - Mota, Maria Carliana (2012)
The residency is a period of professional training that requires a high degree of dedication, with long working hours and shifts performing in-hospital clinical environment. This routine labor is associated with impairment of a healthy lifestyle, with losses eating habits, physical activity level and pattern and quality of sleep. Thus, the residency provides an ideal model to study how working hours can affect the lifestyle and health. The aim of this study was to evaluate the nutritional profile, metabolic and sleep habits of doctors in residency program at the Faculty of Medicine, Federal University of Uberlândia. The study included 72 medical residents (52 women and 20 men) who underwent nutritional assessment (three-day food record analyzed by the Healthy Eating Index-Adapted - IASad), anthropometric measurements (measurements of waist circumference, weight, height, body mass index, BMI), fasting metabolic profile (lipids, cortisol, C-reactive protein (CRP), glucose and insulin; quality and duration of sleep (Sleep quality Score Pittsburgh - PSQI) and excessive daytime sleepiness (Epworth Sleepiness Scale - ESS). It was identified that 33.4% of subjects were overweight or obese (65% among men and 21.1% among women). Men had significantly higher BMI (p = 0.002) and weight gain self-reported after beginning of residence (p = 0.008), when compared with women. Inadequate dietary habits were observed in both genders, including the low consumption of fruits and vegetables and high intake of sweets, cholesterol, caffeine, total fat and saturated fat. The mean ESS values for all volunteers were 11.0 + 3.9 and showed no differences between the genders. The total sleep time differed between the genders (6.7 +1.1 vs. 6.1 +0.9 hours per night). Furthermore, 76.4% of physicians had a poor sleep quality. The average values assigned to the PSQI were above the recommended limits (<5), indicating poor sleep quality (6.2 +2.5 for both genders, 5.9 for women and 7.5 +2.4 +2 2 for men, p = 0.01). Women had higher mean high-density lipoprotein (HDL-C) (p <0.005), CRP (p = 0.04) and cortisol (p = 0.009). Approximately 65% of residents had serum CRP above of the recommended limits. Men had a higher prevalence of hypertriglyceridemia than women (25% versus 6%, respectively). In conclusion, we found a high prevalence of unhealthy outcomes, such as overweight and obesity, poor diet - including inadequate intake of fruits and vegetables and excess cholesterol, fats and caffeine - and high occurrence of excessive daytime sleepiness and sleep quality bad. These results indicate the need to monitor the health status and develop actions to minimize health problems already installed in these individuals.